Digital Technology-Enabled Resource Decoupling and Economic Growth Quality in Ecological Agricultural Integration: Global Pathways - Pang, Ning (Digital Technologies Research and Applications, 2026)
Using the three-proof method combining academic papers, policies, patents and so forth, this paper analyzes and compares 15 representative global cases in depth, and finds out for the first time: (1) An ecological element contribution elasticity coefficient of 0.234 proves that natural capital has its own independent economic value, and globally, the synergetic effect level is 0.86, realizing simultaneous output growth rate of 6%, resource efficiency promotion degree of 0.83. (2) Environment-friendly, economically feasible industrial concept prototypes were discovered, namely dry fermentation (return on investment ROl 196‰), Dutch factory recycling (ROl 164‰), Israel’s water-saving techniques (ROl 246‰) and so forth, with a payback period of 3–5 years, ROl of 18–25 per thousand. (3) The optimal threshold values are found out respectively for technology development intensity, corporate social responsibility fulfillment amount, and farmer diversification proportion rather than assuming that more is always better. Different development path guidance suggestions are provided for different countries/regions according to their actual situations. It is estimated that applying this framework could increase agricultural resource and energy efficiency by 15–25 percentage points and thus help achieve the SDGs of the UN. In future research, attention should also be paid to issues such as evaluation of system resilience under climate change scenarios, application based on blockchain AI technology integration, consideration of how small-scale producers can participate in integration, etc.